Laparoscopic Urologic Surgery in Malignancies - Rosette, Jean J.M.C.H. de la.; Rosette, Jean J.M.C.H. de la.; Gill, Inderbir S.; Gill, Inderbir S. (Springer Berlin Heidelberg : Imprint: Springer, 2005)
The horizons of laparoscopic surgery are expanding, such that the overwhelming majority of abdominal urologic procedures have now been performed laparoscopically. In some of these procedures, the laparoscopic alternative has been demonstrated to be superior to its open counterpart; in others comparative analyses are ongoing; and in yet others, only the initial forays into minimally invasive surgery have been undertaken. This book sets out to collate the current body of knowledge on laparoscopic urology under one cover. The authors are respected experts in the field and have provided concise, thoughtful updates on their respective topics. The information contained in this volume will help urologists to increase their laparoscopic knowledge and skills.